PERANCANGAN SISTEM MONITORING PADA JARINGAN LOAD BALANCING MENGGUNAKAN MUNIN MONITORING - Robertus Desta Raka Siwi; Suwanto Raharjo; Amir Hamzah (Jurnal Jarkom, 2015)
The increasing number of users who have connected to each other sometimes makes a lot of obstacles on the server, such as an increase in the performance of the server process that makes the server down and a lot of running processes. To overcome these problems, merging several servers into a single unit that can work simultaneously for load balancing server is the solution. One method is to use a proper load balancing or load balancing (request) to a web server aims to ease the burden on each server. In addition to cope with the load balancing methods, to keep the server in order to remain stable, the required monitoring network load balancing. In this issue, the monitoring process can be overcome with the addition of Munin to monitor the state of the server. With the addition of munin on the network load balancing, the activity on the server is going down in the event of a server, it can be directly terdeteksi.Munin produce produce a nice graph virtually every aspect of the server (load average, memory usage, CPU usage, traffic eth0 , etc.). Munin provide some information in graphs through a web interface.